Clinical trial: the effect and timing of food on the pharmacokinetics and pharmacodynamics of dexlansoprazole MR, a novel Dual Delayed Release formulation of a proton pump inhibitor – evidence for dosing flexibility - LEE, R. D.; VAKILY, M.; MULFORD, D.; WU, J.; ATKINSON, S. N. (Alimentary pharmacology & therapeutics, 2009)
Summary Background  Dexlansoprazole MR is a proton pump inhibitor with a Dual Delayed Release (DDR) formulation designed to prolong the dexlansoprazole plasma concentration–time profile. The presence of food or time of dosing relative to food may affect dexlansoprazole absorption. Aims  To evaluate the effect of food on the pharmacokinetics (PK) and pharmacodynamics (PD) of dexlansoprazole following oral administration of dexlansoprazole MR. Methods  In this open‐label, single‐dose, randomized, 4‐way crossover study, 48 healthy subjects received placebo (day 1) and dexlansoprazole MR 90 mg (day 3) after fasting, 5 or 30 min before a high‐fat breakfast, or 30 min after a high‐fat breakfast. Intragastric pH (days 1 and 3) and PK (day 3) of dexlansoprazole were assessed over a 24‐h interval after each dose. Results  Following administration of dexlansoprazole MR under fasted/fed conditions, mean dexlansoprazole plasma concentration–time profiles generally exhibited two distinct peaks, resulting from the DDR formulation. Increases in dexlansoprazole maximum plasma concentration (12–31%) and area under the plasma concentration–time curve (9–21%) were observed with the fed regimens; however, differences in intragastric pH were not considered clinically relevant. Conclusion  Dexlansoprazole MR can be administered without regard to food or the timing of food in most patients.